Blood phenylalanine reduction reverses gene expression changes observed in a mouse model of phenylketonuria - Rachna Manek (Nature Portfolio, 2021)
Abstract Phenylketonuria (PKU) is a genetic deficiency of phenylalanine hydroxylase (PAH) in liver resulting in blood phenylalanine (Phe) elevation and neurotoxicity. A pegylated phenylalanine ammonia lyase (PEG-PAL) metabolizing Phe into cinnamic acid was recently approved as treatment for PKU patients. A potentially one-time rAAV-based delivery of PAH gene into liver to convert Phe into tyrosine (Tyr), a normal way of Phe metabolism, has now also entered the clinic. To understand differences between these two Phe lowering strategies, we evaluated PAH and PAL expression in livers of PAHenu2 mice on brain and liver functions. Both lowered brain Phe and increased neurotransmitter levels and corrected animal behavior. However, PAL delivery required dose optimization, did not elevate brain Tyr levels and resulted in an immune response. The effect of hyperphenylalanemia on liver functions in PKU mice was assessed by transcriptome and proteomic analyses. We observed an elevation in Cyp4a10/14 proteins involved in lipid metabolism and upregulation of genes involved in cholesterol biosynthesis. Majority of the gene expression changes were corrected by PAH and PAL delivery though the role of these changes in PKU pathology is currently unclear. Taken together, here we show that blood Phe lowering strategy using PAH or PAL corrects both brain pathology as well as previously unknown lipid metabolism associated pathway changes in liver.